2007
DOI: 10.1136/hrt.2006.106393
|View full text |Cite
|
Sign up to set email alerts
|

Has the publication of cardiac surgery outcome data been associated with changes in practice in northwest England: an analysis of 25 730 patients undergoing CABG surgery under 30 surgeons over eight years

Abstract: Publication of cardiac surgery mortality data in the UK has been associated with decreased risk adjusted mortality on retrospective analysis of a large patient database. There is no evidence that fewer high risk patients are undergoing surgery because mortality rates are published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 20 publications
3
97
0
Order By: Relevance
“…Of these, 15 died on the day of admission or the day after admission (1.3%), 34 died within seven days (3.1%) and 65 patients had died within 30 days (6.3%). The median SCS was five (interquartile range (IQR) [3][4][5][6][7][8]. The median length of stay was four days (IQR 1-11 days).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 15 died on the day of admission or the day after admission (1.3%), 34 died within seven days (3.1%) and 65 patients had died within 30 days (6.3%). The median SCS was five (interquartile range (IQR) [3][4][5][6][7][8]. The median length of stay was four days (IQR 1-11 days).…”
Section: Resultsmentioning
confidence: 99%
“…5 Comparison of mortality in cardiothoracic centres has led to improvements in the standard of care. 6,7 Earlier research showed how a simple scoring model, the Modified Early Warning Score (MEWS), was used to gauge the risk of patients for catastrophic deterioration. 8 However, the proposed model lacked specificity to evaluate the risk of in-hospital death for individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…19,[26][27][28] In general, these reviews found a small decline in mortality following public reporting after controlling for trends in a reduction of mortality; however, individual studies varied in their findings. For example, studies examining the impact of cardiac public reporting programmes on mortality rates found a variable picture: eight studies found a decrease in mortality rates over time, [29][30][31][32][33][34][35][36] while another four studies [37][38][39][40] found no changes in mortality rates over time. Similarly, although most studies examining the impact of public reporting on process indicators found an improvement in hospital quality, this varied from a 'slight' improvement to a 'significant' improvement.…”
Section: Existing Evidencementioning
confidence: 99%
“…We need to understand better the size and nature of the problem nationally and how we compare internationally, to have high quality risk-adjusted outcome data to support decision making, and to counsel patients and their families. This approach has been used with success to drive improvement in cardiac surgery [21]. The need for more outcome data is the basis on which the emergency laparotomy network has been founded [22] and for the forthcoming European Surgical Outcomes Study (EuSoS).…”
mentioning
confidence: 99%